Exposure to severe famine in the prenatal or postnatal period and the development of diabetes in adulthood: an observational study - Wang, Ningjian; Cheng, Jing; Han, Bing; Li, Qin; Chen, Yi; Xia, Fangzhen; Jiang, Boren; Jensen, Michael D.; Lu, Yingli (Diabetologia, 2017)
Aims/hypothesis Limited studies have compared the effect of prenatal or postnatal exposure to different severities of famine on the risk of developing diabetes. We aimed to measure the association between diabetes in adulthood and the exposure to different degrees of famine early in life (during the prenatal or postnatal period) during China’s Great Famine (1959–1962). Methods Data from 3967 individuals were included (a total of 2115 individuals from areas severely affected by famine, 1858 from moderately affected areas, 6 excluded due to missing data). A total of 2335 famine-exposed individuals were further divided into those exposed during the fetal stage, childhood or adolescence/young adulthood. We constructed a difference-in-differences model to compare HbA 1c and fasting plasma glucose among the participants exposed to different degrees of famine intensity at different life stages. Logistic analyses were used as measures of the association between diabetes and the different levels of famine severity at different life stages. Results Individuals who had been exposed to famine during the fetal period, childhood, and adolescence/adulthood and who had lived in a severely affected area had a 0.31%, 0.20% and 0.27% higher HbA 1c , respectively, (all p < 0.01) compared with unexposed individuals. After adjusting for age, sex, smoking status, education level and waist circumference, participants exposed to severe famine during the fetal stage (OR 1.90, 95% CI 1.12, 3.21) and childhood (OR 1.44, 95% CI 1.06, 1.97) had significantly higher odds estimates. Unexposed participants living in severely and moderately affected areas had a comparable prevalence of diabetes (OR 1.22, 95% CI 0.80, 1.87). A significant interaction between famine exposure during the fetal and childhood periods and the level of severity in the area of exposure was found ( p < 0.05). Conclusions/interpretation Exposure to severe famine in the fetal or childhood period may predict a higher HbA 1c and an increased diabetes risk in adulthood. These results from China indicate that both the prenatal and postnatal period may offer critical time windows for the determination of the risk of diabetes.